2020
DOI: 10.47577/tssj.v8i1.701
|View full text |Cite
|
Sign up to set email alerts
|

Study on students' experiences about online teaching during COVID-19 Outbreak

Abstract: The online teaching in colleges and universities during the COVID-19 outbreak is one of the challenges faced by faculty and students during this period especially for colleges and universities that meet the quality assurance standards and under the accreditation process. One of the main requirements of quality standards is to carry out a variety of opinion surveys at different stages among different levels of study, analyze, and then provide recommended solutions based on survey findings. Although many researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…As in the Philippines, online learning activities have opened up opportunities to improve educational methods and shift to emerging technologies [11]. Likewise in Saudi Arabia, the implementation of online learning is planned to be carried out in the long term [12]. In line with that, all countries have made innovations in the world of education, such as Indonesia, China and Malaysia.…”
Section: Resultsmentioning
confidence: 99%
“…As in the Philippines, online learning activities have opened up opportunities to improve educational methods and shift to emerging technologies [11]. Likewise in Saudi Arabia, the implementation of online learning is planned to be carried out in the long term [12]. In line with that, all countries have made innovations in the world of education, such as Indonesia, China and Malaysia.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 20.0% of the students decided to go to a different country to continue their pharmacy study after the long suspension of education in Sudan, possibly because many other countries have better digital infrastructure, and university programmes were immediately shifted from traditional teaching to virtual teaching (Al-Mohair & Alwahaishi, 2020). In agreement with that, 46% reported that they are interested in continuing their study if their program study will be offered online.…”
Section: Impact Of Covid-19 On Pharmacy Students In Sudanmentioning
confidence: 98%
“…Yurt dışında yapılan araştırmalarda, öğrencilerin büyük çoğunluğunun uzaktan eğitimden memnun olduğu ve çevrimiçi eğitim platformunu tercih ettiği saptanmıştır. 34,35 Yapılan araştırmaların sonuçları araştırmamızın bulgusunu destekler niteliktedir. Ülkemizde vaka ve ölüm oranlarının artmasıyla birlikte sokağa çıkma kısıtlaması, mesafe kurallarına uyulması, kalabalık ortamlardan uzak durulması, uzaktan eğitim sistemine geçilmesi gibi toplu karantina uygulaması ve evde kal çağrısı yapılması toplumda kaygı ve korku uyandırmasına sebep olduğu düşünülmektedir.…”
Section: Bulgularunclassified